How Self-Efficacy Drives Innovative Work Behavior: Evidence from Indonesian Higher Education with Knowledge Sharing as a Mediator - Desti Ranihusna; Mirwan Surya Perdhana; Suharnomo (Universitas Negeri Semarang, 2026)
Innovative work behavior (IWB) is an important dimension for higher education institutions in facing global demands. This study examines the effect of self-efficacy on innovative work behavior with knowledge sharing as a mediating variable in 129 lecturers at state vocational colleges with public service agencies in Central Java, Indonesia. A quantitative survey method was employed to collect primary data, which were subsequently analyzed using PLS-SEM. The results showed that self-efficacy significantly influenced knowledge sharing and IWB, and knowledge sharing significantly influenced IWB. In addition, knowledge sharing was proven to partially mediate the relationship between self-efficacy and IWB, with the direct effect remaining significant. These findings indicate that lecturers’ self-confidence contributes directly to innovative behavior. However, its influence can also occur if accompanied by knowledge sharing activities in an academic environment. This study extends Social Cognitive Theory by demonstrating how the environmental component of triadic reciprocal causation operates through knowledge exchange at a public service vocational college in Central Java, Indonesia. This suggests that the burden of the Tridharma (three pillars) and the culture of academic collectivism shape the dynamics between personal confidence and innovative output.